Income Elasticity of Poverty: Estimates for South Asian Countries - Ram, Rati (The Economics and Finance Letters, 2015)
Responsiveness of poverty to growth of income in developing countries is of obvious importance. The responsiveness is usually stated in terms of the magnitude of the so-called growth elasticity of poverty, which has received much attention. Noting that in the vast literature on the topic, there is hardly any study that provides estimates of the elasticity for individual countries, this short paper makes a beginning by reporting the elasticity for six South-Asian countries during the period 1990-2005. Even in this relatively cohesive group, the elasticity shows a huge variability from nearly zero for Bangladesh and 0.35 for India to 4.67 for Pakistan, and illustrates the important point that income growth can translate into poverty reduction at vastly different rates, primary reliance on income growth for poverty reduction does not seem appropriate, and poverty-reducing public policy measures may matter even more than income growth.